Evaluation of fluoride concentration in water filter system for households - Mohd Kamil, Nor Amani Filzah; Bahari, Masitah; Akhbar, Nor Azliza; Mizad, Meizareena (International Journal of Integrated Engineering, 2018)
Drinking water that has good quality is important to sustain human life. If the sources of the drinking water have been contaminated by pollutants, it can give harmful effects to human. Besides of pollutants, good quality of drinking water should have optimum concentration of minerals and one of necessary minerals is fluoride. However, fluoride concentration is less emphasized in factor of purchasing the water filter system. In addition, Malaysians are not aware of the importance of optimum fluoride concentration in their drinking. Water filter system is installed to obtain the good quality of drinking water and needs the maintenance services to ensure the quality of drinking water accomplishes a constant protection. However, the performance of maintenance service is never being measured. Therefore, this study was conducted to measure the fluoride concentration in drinking water for household and evaluate the performance of maintenance service in water filter system. Two residential areas in Johor were involved in data collection. Fluoride concentrations at influent of water filter system were in range of 2.41 mg/L to 3.84 mg/L which were above the permissible limit except for USEPA standard. Concentrations at effluent for before maintenance service were reduced, in range of 0.89 mg/L to 1.28 mg/L, and thus water filter system is necessary to install in Malaysian household. However, very low concentrations were detected after maintenance service, in range of 0.08 mg/L and 0.12 mg/L, and thus the maintenance service needs to be revised to obtain the optimum fluoride concentration.